INSTRUCTIONAL STRATEGIES FOR TEACHING CONTENT AREA VOCABULARY IN THE LANGUAGE CLASSROOM - Sama, Khadijat Muhammad (Sokoto Educational Review, 2020)
The paper attempts to provide instructional strategies for teaching content area vocabulary in the language classroom. In order to arrive at the instructional strategies, a library-based research was conducted. Thus, vocabulary was identified as the inventory of words in a language as such it need to be taught to groom the learner to contend with the challenges the academic environment could provide. Thence, having provided vocabulary teaching methods like word definition, demonstration, antonym, synonym, translation and their likes, the paper underscores the need for the teacher to utilize storytelling, vocabulary pack, cued spelling, contextual redefinition, typically to technical meaning approach and coding polysemous words as instructional strategies for teaching content area vocabulary in the language classroom.